(untitled) (Training and Practice : Journal of Educational Sciences, 2011)
Pedagogical thoughts on child were basic elements in the rhetoric of cultural and countercultural movements at the turn of the 20th century. The child became the carrier of the "better" world (see also the metaphor of "sick society"). That was the reason why people idealized the child, and made theories to save it – which, shortly afterwards, they linked with practice (e.g., school building). The conscious system reform of the 20th century broke the balance between man and nature: people become estranged from themselves – that was a phenomenon of this age, and in line with this process the regression of humanity appeared in the vision of the future. In contrast with these tendencies, in the life reform movement and the reform pedagogies, the child was deemed as a saviour. In my research, I would like to analyze two periodicals: the Népművelés/Új Élet (People ’s Education/New Life) and the Kisdednevelés (Education in Kindergarten). With the help of these journals, I would like to sum up the thoughts on the idea of the child and the perception of children in this period.